2022
DOI: 10.26434/chemrxiv-2022-9zh2v-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-scale Methane Measurements at Oil and Gas Facilities Reveal Necessary Framework for Improved Emissions Accounting

Abstract: Methane mitigation from the oil and gas (O&G) sector represents a key near-term global climate action opportunity. Recent legislation in the United States requires updating of current methane reporting programs for oil and gas facilities with empirical data. While technological advances had led to improvements in methane emissions measurements and monitoring, the overall effectiveness of mitigation strategies rests on quantifying spatially and temporally varying methane emissions more accurately than curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…12 Cusworth et al, 11 sampling a larger number of sites, found that short-lived (<1 month) and long-lived (>1 year) sources were both significant contributors to overall emissions across multimonth and multiyear campaigns. Wang et al also found that for some oil and gas basins, the most common emission duration was <1 h. 13 The variability in emission magnitude and duration requires that a large number of observations be taken to accurately measure and represent these high-emission events.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 Cusworth et al, 11 sampling a larger number of sites, found that short-lived (<1 month) and long-lived (>1 year) sources were both significant contributors to overall emissions across multimonth and multiyear campaigns. Wang et al also found that for some oil and gas basins, the most common emission duration was <1 h. 13 The variability in emission magnitude and duration requires that a large number of observations be taken to accurately measure and represent these high-emission events.…”
Section: ■ Introductionmentioning
confidence: 99%